2014
DOI: 10.14338/ijpt.14-00006.1
|View full text |Cite
|
Sign up to set email alerts
|

Proton Therapy and Concomitant Capecitabine for Non-Metastatic Unresectable Pancreatic Adenocarcinoma

Abstract: Purpose: To review early outcomes for patients enrolled on our institution's protocol (PC01) for patients with unresectable pancreatic cancer, and to test whether the serious adverse event rate could be reduced from 15% (expected) to ,5%. Patients and Methods: Twelve patients were enrolled, but only 11 patients are reported in this analysis. Pathology on all patients was reviewed at University of Florida Health Medical Center in Jacksonville to confirm the diagnosis of pancreatic adenocarcinoma. Unresectabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 16 publications
3
50
0
Order By: Relevance
“…A gap which may possibly be exploited by particle therapy and the further development of systemic therapies such as HAPs. Table 3 demonstrates an improved 2-year OS and MST ranging from 31-50.8% and 18.4-25.6 months [45,50]. The enhanced biological damage of PT radiation dose delivery compared to XRT (i.e., dose reporting) across the studies varies in terms of: RBE, cobalt Gray equivalents (CGE refers to absorbed dose × 1.1 (RBE) to express the biologic effective proton dose), Gray equivalents (GyE refers to proton physical dose (in Gray) × 1.1 (RBE)).…”
Section: Stereotactic Body Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A gap which may possibly be exploited by particle therapy and the further development of systemic therapies such as HAPs. Table 3 demonstrates an improved 2-year OS and MST ranging from 31-50.8% and 18.4-25.6 months [45,50]. The enhanced biological damage of PT radiation dose delivery compared to XRT (i.e., dose reporting) across the studies varies in terms of: RBE, cobalt Gray equivalents (CGE refers to absorbed dose × 1.1 (RBE) to express the biologic effective proton dose), Gray equivalents (GyE refers to proton physical dose (in Gray) × 1.1 (RBE)).…”
Section: Stereotactic Body Radiation Therapymentioning
confidence: 99%
“…Kim To date, while PT clinical results have had a positive impact on MST and OS for pancreatic cancer treatment, no chemoradiation combination has resulted in a statistically significant increase in survival. Investigations into concomitant capecitabine by Sachsman et al [50] and Nichols, et al's [59] reported no acute grade 3 GI toxicities and minimal acute grade 2 GI toxicities (9% and 13.6%, respectively). All 3 patients who received grade 2 acute GI toxicities in Nichols, et al [59] prospective PT trial received anterior and lateral beams.…”
Section: Summary Of Pt Clinical Studies Inmentioning
confidence: 99%
“…In another prospective study of 11 patients by Sachsman et al . (28) using a conventional fractionated regimen (59.4 Gy in 33 fractions) demonstrated a 2-year freedom from local progression rate of 69% and 2-year OS rate of 31%. No significant late effects were reported.…”
Section: Proton and Carbon Ion Therapy For Lapc (Table 4)mentioning
confidence: 99%
“…The University of Florida treated PDAC and ampullary cancers patients neoadjuvantly using doses 59.4 Gy (relative biological effectiveness) in 33 fractions, combined with capecitabine, with a similarly low incidence of gastrointestinal toxicity (89). In a separate phase II trial, the same investigators treated 11 unresectable PDAC patients (90). They reported a median OS of 18.4 months, with 1-and 2-year OS rates of 61% and 31%, respectively.…”
Section: Neoadjuvant Particle Therapymentioning
confidence: 99%